Changes in the ocular surface microbiome of patients with coronavirus disease 2019 (COVID-19) - Lin, Jia; Wang, Jingrao; Feng, Jiaoyang; Zhu, Rui; Guo, Yu; Dong, Yueyan; Zhang, Hong; Jin, Xin (Frontiers in Microbiology, 2024)
Purpose: To elucidate the reasons behind the increased incidence of ocular disease in patients with coronavirus disease 2019 (COVID-19), this study delved deeper into the specific effects of COVID-19 on patients' ocular surface microbiome (OSM) and investigated its relationship with the increased incidence of ocular disease. Methods: In this study, conjunctival sac swabs were collected from 43 participants for 16S rRNA amplicon sequencing. The participants were categorized into three groups based on their COVID-19 status: the control group (C group) consisted of 15 participants who showed no evidence of COVID-19, the experimental group (E group) included 15 participants who tested positive for COVID-19, and the COVID-19 recovery period group (R group) comprised 13 participants. Results: In the comparison of alpha diversity, group E had a higher Shannon, Chao1 and Goods coverage index. When comparing beta diversity, groups E and R were more similar to each other. At the phylum level, although the OSM of the three groups was dominated by Proteobacteria, Actinobacteriota, Bacteroidota and Firmicutes, the compositional proportions were significantly different. At the genus level, the dominant species in the three OSM groups were significantly different, with Pseudomonas becoming the dominant genus in groups E and R compared to group C, and the abundance of Ralstonia decreasing significantly. Conclusion: This study provides additional evidence supporting the association between the OSM and COVID-19, which contributes to our understanding of the potential mechanisms underlying ocular symptoms and complications associated with COVID-19 in the future.